Serum level of cathelicidin LL-37 is increased in euthymic patients with bipolar disorder irrespective of their cardio-metabolic status (Archives of Clinical Psychiatry, 2019)
Background: Antimicrobial peptides are components of the innate immune system. Cathelicidin LL-37 plays an important role in antimicrobial defense, exerts proinflammatory effect and strongly affects the immune system functioning. Our recent study revealed that serum concentration of LL-37 is increased in patients with bipolar disorder. Objectives: The aim of this study is to re-evaluate serum LL-37 levels in patients with euthymic bipolar disorder and in healthy controls, matched for anthropometric and body composition parameters. Methods: 36 adult patients with euthymic bipolar disorder and 68 nondepressed adults were included into the study. Concentration of LL-37 in serum was assessed using ELISA method. Detailed anthropometric measurements, body composition and biochemical analyses were performed. Results: There was a statistically significant difference (p = 0.01) in serum LL-37 level between patients with bipolar disorder (4.97 ± 7.98 ng/mL) and control subjects (1.78 ± 2.69 ng/mL). Discussion: Results of this study indicate that LL-37 serum level is increased in euthymic bipolar disorder patients. We found that this increase could not be attributed to analyzed anthropometric or body composition parameters.